NRFHH 2021
DOI: 10.53365/nrfhh/142607
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological survey of six medicinal plants used in the traditional treatment of urinary tract infections and other infectious diseases

Abstract: Benin has attractive ethnobotanical potential with a vast diversity of medicinal plants widely used to treat human diseases. Urinary tract infections are among the diseases traditionally treated by medicinal plants. Mangifera indica, Bridelia ferruginea, Alstonia boonei, Morodora myristica, Xylopia aethiopica and Zanthoxylum zantoxyloides are six plants used in the traditional treatment of urinary infections in Benin. The general objective of this study was to identify the ethnopharmacological uses of these si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In Benin, the use of medicinal plants is an essential practice of the culture and for the traditional health system. Mangifera indica Linn, Bridelia ferruginea Benth, and Alstonia boonei De Wild are three plants commonly used in the traditional treatment of urinary tract infections in Benin [ 8 ]. Several studies have established the toxicological profile of these plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Benin, the use of medicinal plants is an essential practice of the culture and for the traditional health system. Mangifera indica Linn, Bridelia ferruginea Benth, and Alstonia boonei De Wild are three plants commonly used in the traditional treatment of urinary tract infections in Benin [ 8 ]. Several studies have established the toxicological profile of these plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these plants are heavily used by the pregnant women to treat bacterial infections [ 8 ]. This study evaluated the cytotoxic and teratogenic effects of aqueous and ethanolic extracts of Mangifera indica Linn, Bridelia ferruginea Benth, and Alstonia boonei De Wild on Artemia salina larvae and hen embryos.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to their all-year-round availability and because they contain some essential secondary metabolites responsible for their various therapeutic activities as also alluded to by Agbodjento et al, (2020). Previous studies have also shown that the leaves and fruits are the most used by traditional healers and the choice of plant part used is believed to have little or no negative impact on sustainability and conservation as those plant parts used can easily be regenerated and are usually available all year round (Assogba et al, 2021). The habits of the plant species that are mostly used are shrubs and trees likely because of their all-year-round availability.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the respondents are elderly, aged between 60 years and above representing 40% with others aged between 41-59 representing 38% of the respondents who participated in the study. It is generally held in Africa that elderly people hold knowledge of medicinal plants as ethno-therapeutic agents (Assogba et al, 2021) hence a larger percentage of respondents are elders. Medicinal knowledge of plants represents ancestral knowledge transferred from generation to generation.…”
Section: Discussionmentioning
confidence: 99%